2014
DOI: 10.1645/13-470.1
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Helminths, Ectoparasites, and Chytrid Fungus of an Introduced Population of Cane Toads,Rhinella marina(Anura: Bufonidae), from Grenada, West Indies

Abstract: One hundred specimens of Rhinella marina , (Anura: Bufonidae) collected in St. George's parish, Grenada, from September 2010 to August 2011, were examined for the presence of ectoparasites and helminths. Ninety-five (95%) were parasitized by 1 or more parasite species. Nine species of parasites were found: 1 digenean, 2 acanthocephalans, 4 nematodes, 1 arthropod and 1 pentastome. The endoparasites represented 98.9% of the total number of parasite specimens collected. Grenada represents a new locality record fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…It has become an invasive species in several countries around the world, including islands, with reported occurrences in Australia, the southern United States, Hawaii, Fiji, the Philippines, Taiwan, and Europe. Drake et al (2014) found a high prevalence of infection in 95% of Rhinella marina individuals collected on the Island of Granada. Similarly, Pinhão et al (2009) noted a parasite prevalence of 100% and high abundance of acanthocephalans in a population of Rhinella icterica in Brazil.…”
Section: Discussionmentioning
confidence: 86%
“…It has become an invasive species in several countries around the world, including islands, with reported occurrences in Australia, the southern United States, Hawaii, Fiji, the Philippines, Taiwan, and Europe. Drake et al (2014) found a high prevalence of infection in 95% of Rhinella marina individuals collected on the Island of Granada. Similarly, Pinhão et al (2009) noted a parasite prevalence of 100% and high abundance of acanthocephalans in a population of Rhinella icterica in Brazil.…”
Section: Discussionmentioning
confidence: 86%
“…As indicated above, P. lutzi and P. goodmani are morphologically similar and the cane toad, Rhinella marina (Linnaeus, 1758), the type host of P. lutzi (see Arredondo & Gil de Pertierra, 2009), was introduced into Mauritius between 1936 and 1938 (Cheke & Hume, 2008). Pseudoacanthocephalus lutzi has been reported from a range of amphibian hosts across South America and the West Indies (Arredondo & Gil de Pertierra, 2009; Amin & Heckmann, 2014, Drake et al , 2014; Toledo et al , 2017) but not from any of the other countries where R. marina has been introduced. Barton (1997) reported that only local parasites had been recorded from Australian cane toads and Barton & Pichelin (1999) recorded only P. bufonis from cane toads in Hawaii, thereby supporting the finding that the species P. goodmani is distinct from P. lutzi .…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in the cane toad’s introduced range, adult acanthocephalans ( Acanthocephalus bufonis ) infected the intestinal tract of 47/48 toads in Hawaii [ 25 ], larval Pseudoacanthocephalu s sp. were present in the small intestine of toads in Grenada [ 26 ] and a cystacanth occurred in the intestinal serosa of toads in Grenada [ 26 ]. Within its native range in Central and South America the intestines of R .…”
Section: Discussionmentioning
confidence: 99%